The Assessment Teknologi Industri Batik Tulis Pamekasan Dengan Metode Teknometrik Upaya Peningkatan Daya Saing Pasar - Musoffan ST ME (Journal of Economics Development Issues, 2021)
Batik Tulis Pamekasan market share is getting wider to international levels resulting in intense competition between Batik Pamekasan Small and Medium Enterprises (SMEs) both in the local market and the national market so that a development strategy is needed to increase market competitiveness with the support of technology, information, organization and the ability of workers (human) the good one. Because the business performance of an organization, especially SMEs, is directly affected by technoware and humanware, while orgaware affects business performance indirectly through humanware. The purpose of this study is to measure the technological performance of the Batik Pamekasan SMEs technology using the technometric method to determine business competitiveness, while to provide suggestions or strategy proposals that can be done with a SWOT analysis. The results of the research of Batik Pamekasan SMEs have a TCC value at a sufficient level because 0.3 <TCC≤ 0.6 = sufficient, it means that Pamekasan batik UKM is at the semi-modern level, this is because the transformation process is carried out manually while the information is not all SMEs understand sophistication of technology perfectl